Sistem Informasi Buku Tamu Di Sekretariat DPRD Kabupaten Minahasa Berbasis Web Dengan Metode Prototype - Syalomita Cinta; Gladly Caren Rorimpandey (Jurnal Media Computer Science, 2026)
The Secretariat of the Regional House of Representatives (DPRD) of Minahasa Regency currently still uses a traditional method for recording guest book entries, namely manually using paper. This method leads to several issues, such as inefficiency in data retrieval, the risk of information loss, and difficulty in summarizing visit data. To address these issues, a web-based guest book information system was developed using the prototype software development method. This method was chosen because it allows the system to be developed incrementally with active user participation during the design and evaluation stages. The designed system includes key features such as digital guest data entry, the ability to search for data based on specific criteria, and automatic generation of visit reports. Testing results show that this system can simplify the process of recording and managing guest data at the DPRD Secretariat of Minahasa Regency. With the implementation of this system, it is expected that there will be a significant improvement in work efficiency and data accuracy.